Clinical delineation of a subtype of frontonasal dysplasia with creased nasal ridge and upper limb anomalies: Report of six unrelated patients. Issue 12 (14th November 2017) - Lehalle, Daphné; Altunoglu, Umut; Bruel, Ange‐Line; Arnaud, Eric; Blanchet, Patricia; Choi, Jong‐Woo; Désir, Julie; Kiliç, Esra; Lederer, Damien; Pinson, Lucile; Thauvin‐Robinet, Christel; Singer, Amihood; et al.
Abstract : Frontonasal dysplasias are rare congenital malformations of frontonasal process‐derived structures, characterized by median cleft, nasal anomalies, widely spaced eyes, and cranium bifidum occultum. Several entities of syndromic frontonasal dysplasia have been described, among which, to date, only a few have identified molecular bases. We clinically ascertained a cohort of 124 individuals referred for frontonasal dysplasia. We identified six individuals with a similar phenotype, including one discordant monozygous twin. Facial features were remarkable by nasal deformity with creased ridge and depressed or absent tip, widely spaced eyes, almond‐shaped palpebral fissures, and downturned corners of the mouth. All had apparently normal psychomotor development. In addition, upper limb anomalies, frontonasal encephalocele, corpus callosum agenesis, choanal atresia, and congenital heart defect were observed. We identified five reports in the literature of patients presenting with the same phenotype. Exome sequencing was performed on DNA extracted from blood of two individuals, no candidate gene was identified. In conclusion, we report six novel simplex individuals presenting with a specific frontonasal dysplasia entity associating recognizable facial features, limb and visceral malformations, and apparently normal development. The identification of discordant monozygotic twins supports the hypothesis of a mosaic disorder. Although previous patients have been reported, this is the first series, allowing delineation of a clinical subtype of frontonasal dysplasia, paving the way toward the identification of its molecular etiology.